Świadomość ekologiczna studentów kierunku zarządzanie Uniwersytetu Przyrodniczo- -Humanistycznego w Siedlcach: Enviromental awareness of students faculty of management the University of Natural Sciences and Humanities in Siedlce - Rucińska, Patrycja; Szmurło, Agnieszka (Management and Administration Journal, 2021)
Ecology is very important in life. Unfortunately, the community rarely cares about the environment. It is vitally important to know that one of the objectives of shaping future generations is respect for the environment. First of all, people should start with themselves and follow roles of environment protection. Positive interaction between the environment and man is the way to a better life of each organism in the world, because destroying the environment. Unfortunately, at present the majority of the public only theoretically knows what respect for the environment is, and practical environmental activities are barely visible.